Recruiting, interviewing, selecting & orienting new employees - Arthur, Diane (AMACOM/American Management Association, 2012)
"A comprehensive guide through all four stages of the employment process, Recruiting, Interviewing, Selecting & Orienting New Employees has long been the go-to source for anyone involved in staffing. Now this fully revised and updated fifth edition offers even more in the way of step-by-step guidelines on every aspect of the hiring process, specific interview and reference questions to ask (plus ones to avoid), and information on the latest recruiting strategies and orientation programs. What's more, it provides information on many of today's technological staffing challenges, such as virtual interviews, web-based orientations, electronic files, and social media. Readers will also find legal insight into new FMLA legislation, immigration, and record keeping, as well as ways to establish and adhere to standards of excellence. Written for both HR and non-HR practitioners in any work environment, this book helps you: Determine the competencies required for optimal job performance; Weigh the pros and cons of dozens of traditional and cutting-edge recruiting strategies; Set goals and parameters for both HR and departmental interviews; Keep hiring programs consistent with EEO and federal record-keeping requirements; Ask a powerful mix of question types (competency-based, hypothetical, probing, and open- and closed-ended) to determine who will make the best fit; Use pre-employment testing effectively and fairly; Conduct thorough and revealing reference checks; Create effective departmental and organizational orientation programs. With numerous additions throughout every section, this long depended-upon reference features expanded content on such topics as recruitment sources for special interest groups, electronic recruiting methods, and the three distinct types of orientation: organizational, departmental, and web-based."--Publisher.